Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.euroneuro.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine self-administration produces a persistent increase in dopamine D2High receptors

Abstract: Cocaine addicts are reported to have decreased numbers of striatal dopamine D2 receptors. However, in rodents, repeated cocaine administration consistently produces hypersensitivity to the psychomotor activating effects of both indirect dopamine agonists, such as cocaine itself, and importantly, to direct-acting D2 receptor agonists. The current study reports a possible resolution to this long-standing paradox. The dopamine D2 receptor exists in both a low and a high affinity state, and dopamine exerts its eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 29 publications
6
42
0
Order By: Relevance
“…The increase in D2 High receptors is similar to the increase that has been recently reported by Briand et al (2008) following cocaine self-administration training. It is interesting that the number of nicotine infusions appeared higher in rats that displayed the highest levels of D2 High .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The increase in D2 High receptors is similar to the increase that has been recently reported by Briand et al (2008) following cocaine self-administration training. It is interesting that the number of nicotine infusions appeared higher in rats that displayed the highest levels of D2 High .…”
Section: Discussionsupporting
confidence: 81%
“…It has been recently reported that cocaine selfadministration produces a persistent increase in D2 High , a phenomenon that could explain why cocaine administration produces hypersensitivity to dopamine (Briand, Flagel, Seeman, & Robinson, 2008), while drug addicts have a decreased number of striatal dopamine D2 receptors (Volkow et al, 2009). Interestingly, this increase in D2 High has also been reported following amphetamine sensitization (Seeman, Tallerico, Ko, Tenn, & Kapur, 2002), as well as following ethanol, quinpirole, and phencyclidine sensitization (Seeman et al, 2005).…”
Section: Introductionmentioning
confidence: 87%
“…D1R mediates reward learning in response to palatable food (Hikida et al, 2010), and targeted loss of D1R decreases operant responding for sucrose (El-Ghundi et al, 2003). Sucrose preference is reduced by D2R antagonism (Hsiao and Smith, 1995), whereas upregulated D2R levels in the NAc have been reported in some rodent studies of repeated cocaine administration (Peris et al, 1990;Maggos et al, 1998;Briand et al, 2008). The elevated D1R and D2R levels observed in this study could thus lead to the increased responsiveness to palatable food and cocaine.…”
Section: Sensitized Phenotype Caused By Neuroadaptations Increases Rementioning
confidence: 57%
“…This stability is remarkable, given that extended access to cocaine SA produces significant cognitive deficits and impairments in working memory that can persist for at least one month62636465. Such cognitive impairments have also been observed in humans after two weeks of abstinence66.…”
Section: Discussionmentioning
confidence: 97%